Canina fossa abscess and treatment - Muhammad H. Chanda (DiscoverSys Inc., 2018)
Objective: Canina fossa abscesses are rarely reported in the literature. Tooth infection is often derived from bacteria associated with the abscess. Canina fossa abscesses can lead to the development of secondary abscesses, infection of incisors and canines in the upper jaw and maxillary sinusitis infection.Methods: Odontogenic infections can easily spread throughout the muscles and the face, which can cause abscesses mucolabial or accumulation of pus in the eyelid and face. Results: Patients experienced a history of pain and fever. Physical examination showed enlargement and swelling of the right cheek and panoramic radiographs appear radiolucent on the apex of tooth tip 13. Treatment included an intraoral drainage incision at the apex of the tooth 13 and continued administration of antibiotic therapy.Conclusion: Successful treatments require early recognition, determination of etiological factors, and appropriate medical and surgical management.